2003
DOI: 10.1034/j.1600-0501.2003.140113.x
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical stress in bone surrounding an implant under simulated chewing

Abstract: The concept of reducing nonaxial loading of dental implants has been widely regarded as the standard procedure. The aim of this study was to reveal the biomechanical stress distribution in supporting bone around an implant and a natural tooth under chewing function. Three-dimensional finite element models of the mandibular first molar and the titanium implant both with the mandible in the molar region were constructed. The directions of displacement constraints were determined according to the angles of the cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 11 publications
1
57
0
6
Order By: Relevance
“…All models showed maximum von Mises stress values appearing mainly at the cortical buccal bone around the neck of the implant as a result of an oblique load of 30° to buccal cusp; therefore, a reduction of the non-axial loading to the implant is essential in maintaining biomechanical stress distribution in the supporting bone around the implant (22,23). Standard implant models revealed lower stress values at 41% less than those of the short implant models because the short implants were comprised of less area that could dissipate the tension (18).…”
Section: © C I C E D I Z I O N I I N T E R N a Z I O N A L Imentioning
confidence: 99%
“…All models showed maximum von Mises stress values appearing mainly at the cortical buccal bone around the neck of the implant as a result of an oblique load of 30° to buccal cusp; therefore, a reduction of the non-axial loading to the implant is essential in maintaining biomechanical stress distribution in the supporting bone around the implant (22,23). Standard implant models revealed lower stress values at 41% less than those of the short implant models because the short implants were comprised of less area that could dissipate the tension (18).…”
Section: © C I C E D I Z I O N I I N T E R N a Z I O N A L Imentioning
confidence: 99%
“…4,5 It is showing overwhelming capability and versatility in its application in dentistry. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] This paper reviews past and current practices in the finite element analysis of dental implants. The achievements and limitations of the existing analysis are discussed and the gap in research is identified.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the load generated at the bone in the vicinity of the implant may be determined as gradual decrease load, in a precise sense. Previous studies revealed that the concentration of lateral stress occurred at the peri-implant cortical bone (26), (27) .…”
Section: Discussionmentioning
confidence: 99%